Lobbying and Agricultural Trade Policy in the United States - Gawande, Kishore; Hoekman, Bernard (World Bank, Washington, DC, 2012)
The authors study whether political campaign contributions influence agricultural protection in the United States in the manner suggested by the political economy model of Grossman and Helpman (1994). This is the first attempt to test this model using agricultural data. The authors test the model using a detailed cross-sectional data set of agricultural protection, subsidies, and political action committee (PAC) contributions in the late 1990s. The model is qualitatively affirmed by the data. They make a novel attempt to solve a puzzle about the model's quantitative implications, also found in recent studies. This solution makes the simple model consistent with the complicated decisionmaking process in real world government. The results imply the underpinnings of a political economy equilibrium that will be hard to dislodge.